ANALISIS PENGARUH MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. XYZ - Ramadhan, Tinton (Economic Faculty, Attahiriyah Islamic University, 2017)
This study aims to determine the effect of motivation and organizational commitment toward employee performance in PT. XYZ. This study uses survey method and data collection techniques used is literature study, questionnaires, and interviews. The population in this study was all employees of PT. XYZ (XYZ Print), which amounted to 79 people. This study uses regression analysis mooted simple and multiple regression. The collected data were processed using SPSS 23. The results showed that motivation and organizational commitment has a significant influence on employee performance either partially or simultaneously. Motivation and commitment to the organization to have a greater influence on employee performance if both improved simultaneously rather than partially. Keywords: motivation, organization commitment, employee performance